Implementation of Behavior with Reward Techniques to Increase Learning Interest of Elementary School Students - Hidayah, Nurul; Sholichah, Ima Fitri (Universitas Negeri Medan, 2025)
This study aims to determine the effectiveness of reward techniques based on a behavioristic approach in increasing learning interest in grade 3 students of Almadany Elementary School, Gresik. The subjects of the study were three students who showed low learning interest, indicated by lack of focus, often being thorough, and not completing assignments. The intervention was carried out for six sessions, with rewards in the form of praise (verbal), smiles/thumbs up (non-verbal), and stickers and reward cards (symbolic), every time students showed positive learning behavior. Data were collected through observation, teacher interviews, and documentation of behavioral changes. Analysis was carried out descriptively qualitatively and quantitatively using a behavior change table and the ABC (Antecedent–Behavior–Consequence) framework. The results showed a significant increase in aspects of learning interest, including attention, interest, involvement, and joy. The subjects (ASH, MI, and NRS) became more focused, active, and enthusiastic when learning. The teacher also stated that the classroom atmosphere became more conducive after the intervention. Although changes occur gradually, these findings prove that positive reinforcement is effective in modifying learning behavior, in accordance with behaviorism theory, especially positive reinforcement. The limitations of the study lie in the number of subjects and the short duration of the intervention, so it cannot be generalized. This study recommends a wider variety of rewards, including intrinsic and collaborative rewards, as well as the integration of shaping and chaining methods to form long-term learning habits.